PAX Scientific - Isaacs, Andrew M.; Koelman, Onno (London : SAGE Publications Ltd, 2017)
The PAX Scientific case study is a technology startup case that allows students to discuss how a science-driven invention, theory, or idea can be launched into the commercial marketplace. One of the key issues facing leadership is whether to continue to pursue a licensing strategy for its products versus manufacturing those products and selling them themselves. The case allows students to think through how the company can grow beyond a small family business to a much larger company with much greater revenue and profitability potential.
Originally published: Isaacs, A. M., & Koelman, O. (2006). PAX Scientific. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; PAX Scientific; Small business -- Case studies; Business planning -- Case studies; Technology -- Case studies